Can Preinjury Adversity Affect Postinjury Responses? A 5-Year Prospective, Multi-Study Analysis - Wadey, Ross; Evans, Lynne; Hanton, Sheldon; Sarkar, Mustafa; Oliver, Helen (Frontiers in Psychology, 2019)
Informed by and drawing on both the integrated model of response to sport injury (Wiese-Bjornstal, Smith, Shaffer, & Morrey, 1998) and the biopsychosocial model of challenge and threat states (Blascovich, 2008), this multi-study paper examined whether preinjury adversity affected postinjury responses over a five-year time period. Study 1 employed a prospective, repeated-measures methodological design. Non-injured participants (N=846) from multiple-sites and sports completed a measure of adversity (Petrie, 1992); 143 subsequently became injured and completed a measure of coping (Carver, Scheier, & Weintraub, 1989) and psychological responses (Evans, Hardy, Mitchell, & Rees, 2008) at injury onset, rehabilitation, and return to sport. MANOVAs identified significant differences between groups categorized as low, moderate, and high preinjury adversity at each time phase. Specifically, in contrast to low or high preinjury adversity groups, injured athletes with moderate preinjury adversity experienced less negative psychological responses and used more problem-and emotion-focused coping strategies. Study 2 aimed to provide an in-depth understanding of why groups differed in their responses over time, and how preinjury adversity affected these responses. A purposeful sample of injured athletes from each of the three groups were identified and interviewed (N=18). Using thematic analysis, nine themes were identified that illustrated that injured athletes with moderate preinjury adversity responded more positively to injury over time in comparison to other groups. Those with high preinjury adversities were excessively overwhelmed to the point that they were unable to cope with injury, while those with low preinjury adversities had not developed the coping abilities and resources needed to cope postinjury. Practical implications and future research directions are discussed.